2021
DOI: 10.48550/arxiv.2108.01435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Physics in Space

Alessio Belenchia,
Matteo Carlesso,
Ömer Bayraktar
et al.

Abstract: Advances in quantum technologies are giving rise to a revolution in the way fundamental physics questions are explored at the empirical level. At the same time, they are the seeds for future disruptive technological applications of quantum physics. Remarkably, a space-based environment may open many new avenues for exploring and employing quantum physics and technologies. Recently, space missions employing quantum technologies for fundamental or applied studies have been proposed and implemented with stunning … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 646 publications
(886 reference statements)
0
7
0
Order By: Relevance
“…3 Another experimental test was reported by Stefanov et al in 2002 [100] using time-bin entangled photons separated over 10 km via an optical fiber, and "moving" beamsplitters implemented with acoustooptical modulators. Each incoming photon effectively saw a beamsplitter moving at about 2,500 m/s; as in the previous experiment the actual single-photon detectors themselves were not moving 4 . Again, the experiment found that the entanglement correlations were perfectly preserved without need to consider the time-sequencing of events, in agreement with standard quantum mechanics formalism.…”
Section: Bell Tests Between Frames With Large Relative Velocitiesmentioning
confidence: 78%
See 3 more Smart Citations
“…3 Another experimental test was reported by Stefanov et al in 2002 [100] using time-bin entangled photons separated over 10 km via an optical fiber, and "moving" beamsplitters implemented with acoustooptical modulators. Each incoming photon effectively saw a beamsplitter moving at about 2,500 m/s; as in the previous experiment the actual single-photon detectors themselves were not moving 4 . Again, the experiment found that the entanglement correlations were perfectly preserved without need to consider the time-sequencing of events, in agreement with standard quantum mechanics formalism.…”
Section: Bell Tests Between Frames With Large Relative Velocitiesmentioning
confidence: 78%
“…Alternatively, one can drop the assumption that human choices are purely results of physical processes in the brain, and instead adopt a stance like Cartesian dualism 4 , where one invokes some external non-physical mind that is somehow able to inject events into our 3+1 dimensional spacetime while not being part of it. This is similar to the assumption that is required to close the freedom-of-choice loophole when quantum random number generators are used in the "loopholefree" experiments cited above-a truly novel bit of information enters the world such that a 0 and 1 are both perfectly compatible with identical past light cones.…”
Section: Appendix B: the Human-decision Bell Tests In The Context Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Quantum estimation theory is typically envisioned as a toolbox to design highly precise measurements [1][2][3][4][5]. Discovered over half a century ago [1,[6][7][8][9][10][11][12][13], this framework is currently attracting a great deal of attention due to its central role in 'the second quantum revolution' [14]-an application of the principles of quantum mechanics to sensing, metrology, communication, computation, nano and space technologies [15][16][17][18][19][20][21]. But, beyond its unquestionable value as a practical tool, estimation theory may be attributed a more prominent role within the foundations of physics: it enables the means to connect, in a clear and systematic fashion, the variables that we measure in the laboratory with the variables appearing in our theories of nature.…”
Section: Introductionmentioning
confidence: 99%